Ligustrazine Alleviate Acute Lung Injury Through Suppressing Pyroptosis and Apoptosis of Alveolar Macrophages - Jiang, Rundong; Xu, Jiaqi; Zhang, Yuezhong; Zhu, Xuanmeng; Liu, Jiachen; Tan, Yurong (Frontiers in Pharmacology, 2021)
Ligustrazine (Tetramethylpyrazine, TMP) is an active substance extracted from the Umbelliferae plant Ligusticum chuanxiong. It has been proven to have antioxidant and inflammation effects. The study was designed to explore the efficacy and specific mechanism of TMP for ALI/ARDS treatment. Here, we confirmed that TMP decreased the infiltration of inflammatory cells in alveoli and the secretion of pro-inflammatory factors, which is comparable to glucocorticoids in vivo. In vitro, TMP inhibited the polarization of M1-type macrophages, and to a certain extent, promoted M2-type repolarization, thus reducing LPS-induced massive transcription and secretion of IL-1β, IL-18, TNF-ɑ and other inflammatory factors. Besides, TMP reduced expression of NLRP3, inhibited the formation of inflammasome complexes, and decreased the cleavage of caspase-1, leading to reduced cell pyroptosis and accompanying inflammation. TMP also inhibited apoptosis through caspase-8/caspase-3 signaling pathways. Our study indicates that TMP improved ALI through inhibiting the TLR4/TRAF6/NFκB/NLRP3/caspase-1 and TLR4/caspase-8/caspase-3 signaling pathways, which reversed macrophages polarization, reduced cell pyroptosis and apoptosis, which provides a theoretical basis of using TMP in treating ALI in the future.